In-plane bending behaviour and capacities of S690 high strength steel welded I-section beams. (November 2019) - Sun, Yao; He, An; Liang, Yating; Zhao, Ou
Abstract: The present paper describes an in-depth experimental and numerical investigation into the in-plane flexural behaviour and bending moment capacities of S690 high strength steel welded I-section beams. The experimental investigation was conducted on six different welded I-sections fabricated from the same batch of 5 mm thick S700MC high strength steel hot-rolled plates by means of gas metal arc welding, and involved initial local geometric imperfection measurements and twelve in-plane four-point bending tests, with six performed about the cross-section major principal axes and another six conducted about the cross-section minor principal axes. Following the experimental study, a numerical investigation was performed, where the developed finite element models were firstly validated against the test results and then used to perform parametric studies to generate further structural performance data over a broader range of cross-section sizes. The obtained experimental and numerical results were carefully analysed and then adopted to evaluate the accuracy of the existing slenderness limits (for classifications of plate elements and cross-sections) and local buckling design rules for S690 high strength steel welded I-sections in bending, as set out in the European, Australian and American standards. The results of the evaluation revealed that the codified slenderness limits are generally safe when used for the classification of the constituent plate elements of the examined S690 high strength steel welded I-section beams, except for that given in the American specification for slender/non-slender outstand elements in compression. All of the three considered design standards were shown to yield accurate cross-section bending moment capacity predictions for compact (Class 1 and 2) S690 high strength steel welded I-section beams bent about both the principal axes and non-compact (Class 3) S690 high strength steel welded I-section beams bent about the major principal axes, but resulted in a rather high level of conservatism in predicting the cross-section bending moment capacities for non-compact (Class 3) S690 high strength steel welded I-sections in bending about the minor principal axes and slender (Class 4) S690 high strength steel welded I-sections subjected to both major-axis bending and minor-axis bending. Highlights: In-plane bending behaviour and capacities of grade S690 high strength steel welded I-section beams were investigated. Twelve in-plane four-point bending tests were conducted, with six performed about each principle axis. Finite element models were developed and validated against test results, and then used to perform parametric studies. The accuracy of the codified slenderness limits for S690 high strength steel welded I-section beams was assessed. Evaluation of the codified bending moment capacities for S690 high strength steel welded I-section beams was conducted.